Pemberdayaan Kader Kesehatan dalam Upaya Pendampingan Keluarga Stunting melalui Peningkatan Kemampuan Mengelola PMT Berbasis Sumber Pangan Lokal di Desa Wargakerta, Kecamatan Sukarame, Kabupaten Tasikmalaya - Agi Ahmad Gifari; Siti Fatimah; Anita Dyah Deswita; Alika Arifiyani Ferbianti; Hamilatul Ulya; Putri Dzakiyya Lisdinawati; Deborah M M Nababan; Andy Muharry (Lembaga Pengembangan Kinerja Dosen, 2024)
The problem of stunting as a chronic nutritional issue in Indonesia requires special attention, especially in areas with abundant local food potential such as Wargakerta Village, and Tasikmalaya Regency. The health care empowerment program is carried out to increase community participation in preventing stunting through managing local food-based supplementary feeding (PMT). This activity involved 28 health cadres, using outreach methods, showing video demonstrations of making tilapia fish nuggets and providing PMT recipes based on local resources. Pre-test and post-test evaluations showed an increase in cadre knowledge of 89% after the activity. Statistical analysis using the Wilcoxon test produces a p-value of 0.000, which indicates a significant difference before and after counseling. This program proves that innovations based on local food, such as tilapia fish nuggets, can increase health cadres' knowledge in supporting the growth and development of toddlers and reduce the risk of stunting